Can pediatric bipolar disorder be successfully treated when comorbid with conduct disorder? A secondary analysis of clinical trials of risperidone, olanzapine, quetiapine, ziprasidone, and aripiprazole. (May 2022) - Wozniak, Janet; DiSalvo, Maura; Farrell, Abigail; Yule, Amy; Joshi, Gagan; Cook, Emmaline; Faraone, Stephen V; Biederman, Joseph
Background: Pediatric bipolar disorder (BP) is frequently comorbid with conduct disorder (CD) and its presence adds to the morbidity of BP. While there are no known pharmacological treatments for CD, pediatric BP is responsive to treatment with medications initially indicated for the treatment of psychosis, several of which have Food and Drug Administration (FDA) approval for the treatment of pediatric mania. Aims: The main aim of this secondary analysis was to examine whether pediatric BP comorbid with CD responds similarly to treatment with such selected medications. Considering the well-documented morbidity of CD, this finding could have important clinical and public health significance. Methods: We conducted a secondary analysis of six prospective 8-week open-label trials of selected medications (risperidone, olanzapine, quetiapine, ziprasidone, and aripiprazole) using identical methodology in youth with BP with and without comorbid CD. Results: Of 165 youths with BP, 54% ( N = 89) met criteria for comorbid CD. The antimanic effects observed did not significantly differ between BP youths with and without comorbid CD, as measured either by a reduction in Young Mania Rating Scale (YMRS) ⩾ 30% or Clinical Global Impression (CGI)-Improvement ⩽ 2 ( p = 0.23), or by the more stringent definition of a reduction in YMRS ⩾ 50% ( p = 0.61). Conclusion: Pediatric BP can be effectively treated with the abovementioned medications in the context of comorbid CD. Based on previous research showing that remission of BP is associated with remission of CD, if confirmed, these findings raise the possibility that antimanic treatment of youth with BP comorbid with CD could have secondary benefits in mitigating the morbidity associated with CD. This is a pilot scale finding, the results of which are promising and should be confirmed by larger and long-term follow-up studies.